Sintesis hidroksiapatit berukuran nano dengan metode elektrokimia dibantu EDTA - Adrian Nur; Desi Liah Martasari; Desy Nurwijayanti; Samsudin Affandi; Arief Widjaja; Heru Setyawan (Jurnal Teknik Kimia Indonesia, 2013)
EDTA-assisted synthesis of nanosized hydroxyapatite by electrochemical method.Synthesis of nanosized hydroxyapatite by electrochemical method has been studied. The aim of this work is to study the effects of variuos parameters on hydroxyapatite particles. The electrochemical synthesis was prepared in solution Ca2+/EDTA/PO43 at concentration 0.25/0.25/0.15 M. The solution was electrolized by using constant direct current at certain current density. There were two treatments for particles after electrosynthesized, namely without aging or aged for 3 days at 40oC. For both cases, the particles  were filtered and washed by demineralized water to eliminate the impurities and unreacted reactans. Then, the particles were dryed at 40oC for 2 days. The dryed particles were characterized by X-Ray diffraction, surface area analyzer, scanning electron microscopy, Fourier transform infrared spectra and thermogravitimetric and differential thermal analysis. The results showed that nanosized hydroxyapatite were produced by electrochemical method. The produced particles were composed of needle-like or plate-like morphologies with equivalent diameter 19-143 nm. The produced particles diameters were inversely proportional to current density, duration of electroysis and EDTA concentration, and proportional to the distance between two electrodes and temperature. The product calcium phosphates types depended on the final pH of electrolysis process and aging treatment. It would tend to hydroxyapatite if pH>8 and brushite if pH<8.Keywords: hydroxyapatite, nanoparticle, electrochemical, synthesis, characterize AbstrakPenelitian tentang sintesis hidroksiapatit berukuran nano dengan metode elektrokimia telah dilakukan. Penelitian ini bertujuan  mempelajari pengaruh kondisi operasi terhadap pembentukan partikel hidroksiapatit.Elektrosintesis dilakukan dengan menggunakan larutan Ca2+/EDTA/PO43- 0,25/0,25/0,15 M. Ada dua perlakuan sebelum penyaringan yaitu langsung disaring dan dibiarkan dulu selama 3 hari pada 40oC (proses penuaan). Endapan yang dihasilkan kemudian disaring dan dicuci dengan air demin untuk menghilangkan pengotor dan sisa reaktan yang tidak bereaksi. Endapan dikeringkan dengan suhu 40oC selama 2 hari untuk selanjutnya dikarakterisasi. Hasil menunjukkan bahwa dengan metode elektrokimia bisa dihasilkan partikel hidroksiapatit berukuran nano. Partikel yang dihasilkan berbentuk jarum atau plat dengan diameter BET 19-143 nm. Diameter partikel yang dihasilkan berbanding terbalik dengan kenaikan rapat arus, waktu elektrolisa dan konsentrasi EDTA. Sebaliknya, diameter partikel berbanding lurus dengan jarak elektrode dan suhu. Selain itu jenis partikel yang dihasilkan sangat bergantung pada pH akhir dari proses elektrolisis maupun perlakuan penuaan, dimana pH>8 cenderung membentuk HA, sedangkan pH<8 cenderung membentuk fasa brushit.Kata kunci:hidroksiapatit, nanopartikel, elektrokimia, sintesis, karakterisasi